Bile duct injury after laparoscopic cholecystectomy: the value of endoscopic retrograde cholangiopancreatography. - Davids, P H (1993)
This study describes the value of endoscopic retrograde cholangiopancreatography (ERCP) in patients with bile duct injury after laparoscopic cholecystectomy. Twelve consecutive patients were studied over a one year period. In all patients the biliary tree was visualised during ERCP. Four patients had complete bile duct obstruction, seven patients had a stricture (two with concomitant leakage), and one patient had leakage from a hepatic branch. Three patients with complete obstruction, presented with a relatively prolonged symptom free, 'silent' period before diagnosis. In all four patients with complete transection, a proximal hepaticojejunostomy was performed. In one patient with a tough fibrous stricture, secondary to incorrect clip placement, passage of the guidewire was impossible, leaving surgical reconstruction as the only therapeutic option. All remaining seven patients with leakage or strictures, or both were successfully treated by endoscopic sphincterotomy only (n = 1) or sphincterotomy and subsequent stent placement (n = 6). When patients do not recover uneventfully after laparoscopic cholecystectomy even without cholestasis or jaundice, early ERCP is recommended as a safe and valuable method to detect bile duct injury and to suggest treatment. Subsequently, more than half of such patients can be treated endoscopically. Extended follow up is needed to evaluate the longterm results.